Nanomaterials Based on Fe3o4 and Phthalocyanines Derived from Cashew Nut Shell Liquid - Casagrande-Denardin, J (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
In this work we report the synthesis of new hybrid nanomaterials in the core/shell/shell morphology, consisting of a magnetite core (Fe3O4) and two consecutive layers of oleic acid (OA) and phthalocyanine molecules, the latter derived from cashew nut shell liquid (CNSL). The synthesis of Fe3O4 nanoparticle was performed via co-precipitation procedure, followed by the nanoparticle coating with OA by hydrothermal method. The phthalocyanines anchorage on the Fe3O4/OA core/shell nanomaterial was performed by facile and effective sonication method. The as obtained Fe3O4/OA/phthalocyanine hybrids were investigated by Fourier transform infrared spectroscopy, X-ray diffraction, UV-visible spectroscopy, transmission electron microscopy (TEM), thermogravimetric analysis and magnetic measurements. TEM showed round-shaped nanomaterials with sizes in the range of 12–15 nm. Nanomaterials presented saturation magnetization (Ms) in the 1–16 emu/g and superparamagnetic behavior. Furthermore, it was observed that the thermal stability of the samples was directly affected by the insertion of different transition metals in the ring cavity of the phthalocyanine molecule. © 2019 by the authors
Keywords: nanomaterials; cashew nut shell liquid (CNSL); phthalocyanines; superparamagnetic